2017
DOI: 10.11606/s1518-8787.2017051006775
|View full text |Cite
|
Sign up to set email alerts
|

Validade de peso, estatura e IMC referidos por puérperas do estudo Nascer no Brasil

Abstract: OBJECTIVE To evaluate the accuracy of information on pre-gestational weight, height, pre-gestational body mass index, and weight at the last prenatal appointment, according to maternal characteristics and sociodemographic and prenatal variables.METHODS The study was developed using data from the face-to-face questionnaire and prenatal card (gold standard) of the study “Birth in Brazil, 2011–2012”. To evaluate the differences between the measured and self-reported anthropometric variables, we used the the Krusk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
1
8
0
2
Order By: Relevance
“…They compared self-reported with measured first-trimester weight and concluded that women tended to underestimate their weight but the effect of this underestimation on BMI classification was limited. Araújo et al [ 14 ] observed the same pattern of underestimation of self-reported pre-pregnancy weight in their study of 17,093 pregnant women from the whole country. It is important to mention, however, that the agreement between self-reported pre-pregnancy weight and weight at different times during the first trimester of pregnancy was not evaluated in those studies.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…They compared self-reported with measured first-trimester weight and concluded that women tended to underestimate their weight but the effect of this underestimation on BMI classification was limited. Araújo et al [ 14 ] observed the same pattern of underestimation of self-reported pre-pregnancy weight in their study of 17,093 pregnant women from the whole country. It is important to mention, however, that the agreement between self-reported pre-pregnancy weight and weight at different times during the first trimester of pregnancy was not evaluated in those studies.…”
Section: Introductionsupporting
confidence: 53%
“…In their systematic review, Headen et al [ 11 ] observed a high correlation between self-reported and early-pregnancy weight, despite a tendency toward underreporting of pre-pregnancy weight among the 33 identified studies. In the three studies conducted in Brazil, a high correlation and agreement between self-reported and measured weight and a tendency toward underestimation was also observed [ 12 14 ]. However, these studies did not consider the timing of the first-trimester weight measurement and the possibility of weight gain/loss during this period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal self-report of prepregnancy weight has a high level of accuracy for purposes of calculating BMI, and the minimal underestimations that occur do not heavily impact BMI categorizations. 22 , 23 We considered 4 categories of maternal BMI, according to the international classification: underweight was defined as BMI less than 18.5; reference range, BMI 18.5 to less than 25; overweight, BMI 25 to less than 30; and obesity, BMI 30 or greater. 24 To ensure that our findings regarding prepregnancy BMI did not derive primarily from other maternal factors that have been associated with fetal growth, we controlled for maternal weight gain and metabolic or health complications during pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have found good agreement between measured and maternal recall pre-pregnancy weight information. 25,26 Additional exploratory analyses (in 1993 Birth Cohort databases) were conducted to estimate the agreement between G2 body weight measured at 15, 18 and 22 years of age follow-up visits as compared to G2 recalled pre-pregnancy weight. G3 age was considered to select the follow-up closest to the period before G2 pregnancy: <3 years of age (G2 follow-up at 22 years), 3 to 5 years (G2 follow-up at 18 years), and ≥6 years (G2 follow-up at 22 years).…”
Section: Independent Variablesmentioning
confidence: 99%